2015
DOI: 10.1186/s12864-015-1804-x
|View full text |Cite
|
Sign up to set email alerts
|

ALOMYbase, a resource to investigate non-target-site-based resistance to herbicides inhibiting acetolactate-synthase (ALS) in the major grass weed Alopecurus myosuroides (black-grass)

Abstract: BackgroundHerbicide resistance in agrestal weeds is a global problem threatening food security. Non-target-site resistance (NTSR) endowed by mechanisms neutralising the herbicide or compensating for its action is considered the most agronomically noxious type of resistance. Contrary to target-site resistance, NTSR mechanisms are far from being fully elucidated. A part of weed response to herbicide stress, NTSR is considered to be largely driven by gene regulation. Our purpose was to establish a transcriptome r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 83 publications
4
73
0
Order By: Relevance
“…A general review of the literature (Tables and S1) reveals a wide array of RNA‐seq experimental set‐ups employed by weed researchers over the last few years . These initial set‐up decisions can drastically influence the number of transcripts that appear as significantly differentially expressed by the end of the analysis.…”
Section: Lessons From the Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…A general review of the literature (Tables and S1) reveals a wide array of RNA‐seq experimental set‐ups employed by weed researchers over the last few years . These initial set‐up decisions can drastically influence the number of transcripts that appear as significantly differentially expressed by the end of the analysis.…”
Section: Lessons From the Literaturementioning
confidence: 99%
“…All three studies that attempted to control for the genetic background produced shorter DET lists, even when the number of replicates was low. In fact, one of these studies compared only one pooled HR sample with one pooled HS sample and produced 1310 DETs . Other studies with a single replicate returned much longer DET lists, with an average of 44 000 DETs returned in those papers .…”
Section: Lessons From the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the transcriptional response to ALS inhibitors of A. myosuroides (black‐grass) was found consistent with the physiological effects of these herbicides observed in broad‐leaved species (Gardin et al ., ). This suggested that pathways involved in ALS‐inhibitor response may be conserved in plants.…”
Section: Introductionmentioning
confidence: 97%